Using D-optimal experimental design to optimise remazol black B mineralisation by Fenton-like peroxidation - Hasan, D.B.; Abdul Raman, Abdul Aziz; Daud, Wan Mohd Ashri Wan (Taylor & Francis, 2012)
The mineralisation of remazol black B (RBB) was studied at concentrations ranging from 20-1000 mgL(-1). The work was aimed at investigating the Fenton-like peroxidation of RBB at a concentration typically obtained in Batik cottage industries. Other response parameters were degradation and colour removal efficiencies. The parameters that were measured included total organic carbon (TOC), chemical oxygen demand (COD) as well as absorbance for mineralisation, degradation and colour. To optimise the process, the interaction effects of several controlling variables on the treatment process were examined using dispersion matrix-optimal design and response surface analysis. Four specific variables: initial dye concentration (Dye)o; the molar ratio of oxidant to dye organic strength (H2O2):(COD); the mass ratio of the oxidant to the catalyst (H2O2):(Fe3+) and reaction time (t(r)), were observed. Three reduced empirical models, one for each response, were developed for describing the treatment process. For 20, 510 and 1000 mgL(-1), the optimum TOC reduction and oxidation times were 44 for 95 min, 52 for 52.5 min and 68 for 10 min corresponding to 67, 81 and 75 COD reduction, respectively. The optimum COD reduction and oxidation times were 89 for 95 min, 91 for 10 min and 84 for 95 min for concentrations of 20, 510 and 1000 mg L(-1), respectively. For all concentrations, total colour removal was achieved. A comparison of the results obtained in this study with literature values for traditional Fenton, photo-Fenton and photo-Fenton-like oxidation indicated that the TOC reduction obtained using the Fenton-like process was satisfactory.